Analysis of Financial Statement Preparation Efficiency through the Utilization of the Olsera Application at Arfath Store MSME, Semarang - Reyhan Adi Nugroho; Supandi; Ade Ricky Rozzaqi (Cattleya Darmaya Fortuna, 2026)
This study aims to analyze the efficiency of financial statement preparation through the utilization of the Olsera application at Arfath Store MSME in Semarang. A descriptive qualitative approach with a case study design was employed to gain an in-depth understanding of the mechanisms and practical impacts of the system's implementation in the business environment. Data were collected through passive participant observation, semi-structured interviews, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña (2014), which consists of data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation, method triangulation, and member checking. The findings reveal that the utilization of Olsera has improved efficiency across six key indicators: report preparation speed, process convenience, reduction in recording errors, savings in administrative workload, ease of access to financial data, and integration of transaction data. Quantitatively, the time required to prepare daily financial statements decreased from 3-5 hours to less than 15 minutes. These findings highlight the importance of adopting digital accounting technologies among MSMEs and recommend optimizing Olsera’s financial reporting features accompanied by structured training programs for users.